PENGARUH KONTROL DIRI, LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP PERILAKU MENABUNG MAHASISWA PRODI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PASIR PENGARAIAN - Hendra; Andi Afrizal (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of self control, financial literacy and financial inclusion on the saving behavior of students of the Management Faculty of Economics, University of Pasir Pengaraian partially simultaneously. The population of this study is the students of Management Study Program, Faculty of Economics, University of Sandy Pengaraian. The sampling method using purposive sampling technique. The analysis technique used is multiple linear regression analysis using the SPSS program. The results of the study based on multiple linear regression analysis showed that self-control, financial literacy and financial inclusion had a positive and significant effect on saving behavior with a coefficient of 1.203. Partially the variables that influence saving behavior are self-control and financial inclusion, while simultaneously the variables of self-control, financial literacy and financial inclusion together influence the saving behavior of students of Management Study Program at the Faculty of Economics, University of Pasir Pengaraian.